Most Global Gauging Stations Present Biased Estimations of Total Catchment Discharge - Peng Huang; Genxu Wang; Li Guo; Carlos R. Mello; Kai Li; Jiapei Ma; Shouqin Sun (Geophysical Research Letters, 2023)
Abstract Stream gauging stations provide critical streamflow measurements for hydrological applications; however, they may not accurately capture total catchment discharge due to unmonitored regional groundwater flow. Here, we evaluate the effectiveness of streamflow data from gauging stations worldwide to represent total catchment discharge through a modified hydrological model that includes baseflow signatures to constrain groundwater flow processes. We find that approximately 70% of gauging stations present biased estimations of total catchment discharge (bias >10%). This result implies that hydrology‐related processes may not be fully understood, and misleading conclusions may be drawn owing to the low streamflow measurement effectiveness. By influencing subsurface hydrological processes, catchment factors, including catchment area, topography, climate, and geological features, are linked to the effectiveness of streamflow measurements. Our findings highlight the importance of accurate streamflow measurement effectiveness for obtaining a reliable understanding of catchment hydrological processes to support sustainable water resource management.